Epidemiological Features of Pandemic Influenza in Kyrgyzstan due to Influenza A(H1N1)pdm - K. T. Kasymbekova; Z. S. Nurmatov; A. B. Komissarov; A. V. Fadeev; D. V. Pereyaslov; L. S. Karpova; G. N. Saparova (Эпидемиология и вакцинопрофилактика)
Relevance. Virological laboratory of the Department of prevention of diseases and Sanitary Inspection Healthcare Ministry f of the Kyrgyz Republic is nominated as the National Centre for Influenza Surveillance and accreditated by WHO, and in 2009 is included into a global network of influenza Goal. The purpose of this study - Assessment of epidemic features of manifestations of pandemic influenza A (H1N1) pdm09 in 2009 on the territory of the Kyrgyz Republic, as a comparative study of the molecular and genetic characteristics of influenza A virus (H1N1) pdm09, circulating on the territory of the Republic and the influenza virus reference strains recommended WHO for inclusion in the vaccine for the northern hemisphere. Materials and methods. On the basis of long-term retrospective analysis of the incidence of influenza and severe acute respiratory infections (SARI), and sentinel epidemiological surveillance (SS) data studied pandemic especially in Kyrgyzstan due to influenza A(H1N1)pdm09. Comparative molecular genetic characteristics of influenza viruses A(H1N1)pdm09 allocated in Kyrgyzstan, with reference strains recommended by the World Health Organization (WHO) for inclusion in the vaccine. Results. Overall, the analysis of the results of laboratory tests carried out as part of the routine and sentinel surveillance showed that from January 2009 to March 2010 at 38.8% of those surveyed from among, influenza viruses (at 655 out of 1687) were found. From January to April 2009 in the main circulating influenza A virus (H3N2), which accounted for 55.9 - 77.9% of the number of positive findings. Seasonal influenza A virus (H1N1) was detected in January - February (35.3 and 13.4%, respectively). The share of the flu virus in January accounted for 8%, in March-April - 25%. Not typeable influenza A virus was detected in February in 8.7% of cases. Conclusions. The results of the molecular genetic and virological studies have shown that the influenza pandemic in 2009 in the Republic was due to the spread of pandemic influenza virus A (H1N1) pdm09.